PENGARUH PERSEPSI NILAI TERHADAP NIAT MEMBELI DENGAN MATERIALISME SEBAGAI PEMODERASI PADA PRODUK PALSU MEREK NIKE DIKALANGAN MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS SYIAH KUALA BANDA ACEH - Fandika Maulana; Syafruddin Chan (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2019)
Abstract: This study aims to determine the effect of the perceived value on the purchase intention with materialism as a moderating on Counterfeit product of Nike brand. The empirical study was conducted on the students of the Faculty of Economics and Business of Syiah Kuala University of Banda Aceh. Data collection equipment used in this research is questionnaires, the sample used in this study amounted to 100 people who are students of the Faculty of Economics and Business Syiah Kuala University. Nonprobability Sampling is used as sampling technique with Purposive Sampling method. Interaction Test Method, Test Method of Absolute Difference Value, and Residual Test Method is used as data analysis method using IBM SPSS 20 software. The results of this study indicate that the perceived value has a positive and significant effect on Purchase Intention. In addition, the result is that the materialism variable is not moderating the influence of perceived value on the purchase intention of Counterfeit product of Nike brand. Keywords: Counterfeit Products, Perceived Value, Materialism and Purchase Intention.